Controllability and persistence of money market rates along the yield curve: evidence from the euro area - Ulrike Busch; Dieter Nautz (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2009)
Controllability of longer-term interest rates requires that the persistence of their deviations from the central bank's policy rate (i.e. the policy spreads) remains sufficiently low. This paper applies fractional integration techniques to assess the persistence of policy spreads of euro area money market rates along the yield curve. Independently from anticipated policy rate changes, there is strong evidence for all maturities that policy spreads exhibit long memory. We show that recent changes in the operational framework and the communication strategy of the European Central Bank have significantly decreased the persistence of euro area policy spreads and, thus, have enhanced the central bank's in influence on longer-term money market rates.
Keywords: C22; E43; E52; 330; Long memory and fractional integration; controllability and persistence of interest rates; new operational framework of the ECB